LINGUISTIC PROCESSES IN GEORGIAN MEDIA AND LITERATURE OF XXI CENTURY - Mirtskhulava, Lela; Mashia, Nino (Sworld-Us Conference proceedings, 2023)
The 21st century Georgian media, media and modern Georgian literary language relations need a complex research. Those social, or political changes, which have developed in the 90s of the last century, have significantly changed the structure and lexical f